GLOBAL ACCOUNTING REGULATION: IMPACT OF IFAC ON FINANCIAL REPORTING QUALITY - Popoola, Ayeni; Adeyemi, Aina; Temitope, Ibitoye (International Journal of Engineering Technologies and Management Research, 2017)
This paper provides an analysis of various dimensions of accounting and corporate governance that have led to the currently troubling state of affairs in the financial reporting environment. Good Corporate Governance (GCG) is a mandatory requirement in today’s corporate world by every stakeholder groups. Failure of giant corporate groups in the last twothree decades strengthens the demand further. And surprisingly, in some of such failures, accounting as a discipline is held liable. The way accounting is practiced or the interpretations that may give different prescriptions in similar situations are some dark areas that may open some scope for the corrupted accountants. The paper covers the concept of corporate governance, its legal framework, its current status and how accounting may be practiced to protect corporates from corruption by establishing governance. The paper analyzes how IFAC is succeeding as an international standard setter with an established place in the global financial infrastructure and it reveals a growing reliance on governance by experts together with a growth in influence of the large, multinational accounting firms. Until corporate boards are truly independent of corporate management and are knowledgeable enough to act as effective shareholder advocates, changes in accounting will be of limited impact.